MITOS-MITOS PENGHALANG PERKAWINAN PADA ADAT JAWA DALAM PRESPEKTIF HUKUM ISLAM - Kholik, Kusnul (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2019)
Marriage according to the Javanese is a sacred procession. So it is necessary to consider the calculations and customary battles with great care and caution. Basically, the existence of caution in marriage for the Javanese people show that the Javanese consider marriage to be an important event in human life. The consequence of this assumption is the emergence of hope to achieve happiness in the household. With an ideal type coveted from his soulmate, people will be optimistic to be able to realize the ideals and happiness of his life. In order to achieve such happiness, in the context of the marriage of the Javanese community, they were very concerned about the safety and continuity of marriage, so that in the end they could be classified as lucky (lucky) based on the principle of reciving and submission. Therefore not a few are then trapped into things that are mystical and mythical.